A Note on the Relation between Frames, Perceptions, and Taxpayer Behavior* - JACKSON, SCOTT B.; HATFIELD, RICHARD C. (Contemporary Accounting Research, 2005)
Abstract In this study, we incorporate taxpayers' threat /opportunity perceptions into our analysis of taxpayer behavior in order to refine and extend our understanding of the internal cognitive forces that shape taxpayer behavior. Decision‐making frames (that is, the gain and loss domains from the prospect theory value function) and individual perceptions (that is, perceptions of decision alternatives as being threats or opportunities) are both likely to influence behavior, yet prior research has generally ignored the behavioral effects of individual perceptions. The results of our experiment reveal that taxpayers who are due a tax refund (owe additional taxes) prior to considering a judgemental tax deduction tend to perceive the conservative (aggressive) tax deduction to be more of an opportunity/less of a threat. In turn, we find that taxpayer frames have a direct effect on taxpayer behavior and an indirect effect on behavior through their effect on taxpayers' threat/opportunity perceptions. Perhaps the most important message of this study is that researchers can advance our understanding of the internal cognitive processes that shape taxpayer behavior by incorporating taxpayer perceptions into their research designs.